Local Efforts in Housing Provision - Rosario G. Manasan; Anicia C. Sayos; Ross Q. Quisao (Philippine Institute for Development Studies (PIDS), 1998)
From the provision of the Local Government Code, various LGUs have provided the housing requirements of the less-privileged sectors. This paper presents an overview of the existing knowledge and policy experience in local housing innovations in the cities of Palawan, Naga and San Carlos. It also highlights the key concerns and issues gathered from the experience of these cities.
Keywords: 330; governance; housing program; Local Government Units (LGUs)